STUDI EKOLOGI Anopheles balabacensis DI DAERAH DENGAN ATAU TANPA KEBUN SALAK DI KABUPATEN BANJARNEGARA - Bambang Yunianto; Bina Ikawati; Sunaryo Sunaryo (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2009)
Banjarnegara district is one of the district which have malaria problem in Central Java. According to SLPV survey (2000-2001), the pattern of malaria increasement is similar with the pattern of Anopheles balabacensis density. Besides, An. balabacensis is a potential vector at a recent infected area and the location with malaria outbreak (KLB). Until now there is no complete study about bioecology of An. balabacensis in Banjarnegara district. This is why we conduct the study about bioecology of An. balabacensis with three location based on endemicity strata, salak field present and An. balabacensis present. The result of this study is expected to give a basic information for vector control programme in order to cut malaria infection chain.This study was observational with ecological study design. Population of this research covered the community and breeding place of Anopheline mosquito which was found in research location. While the sample is the population of An. balabacensis and its breeding places that found in research location.Anopheles balabacensis was found in location with salak predominantly i.e. Kendaga Village, Banjarmangu Subdistrict with MBR 0,05; Prigi Village, Sigaluh Subdistrict MBR 0,03; while at location without salak predominantly in Badakarya Village, Punggelan Subdistrict An. balabacensis was not found. The presence of salak vegetation tends to influence the presence of An. balabacensis, because its leaves give a shaded breeding place for An. balabacensis. Suggestion for malaria program organizer are always be aware of the presence of malaria infection by tightening migration surveillances and eliminating water seepages. Spacing plant and setting the number of salak rib between 7 to 9, cultivating larvarous fish or giving altosid at wellspring contain mosquito larvae.